2022
DOI: 10.3390/chemosensors10100408
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Dielectric Spectroscopic Detection of Aliphatic Alcohol Vapors with Surface-Mounted HKUST-1 MOFs as Sensing Media

Abstract: We leveraged chemical-induced changes to microwave signal propagation characteristics (i.e., S-parameters) to characterize the detection of aliphatic alcohol (methanol, ethanol, and 2-propanol) vapors using TCNQ-doped HKUST-1 metal-organic-framework films as the sensing material, at temperatures under 100 °C. We show that the sensitivity of aliphatic alcohol detection depends on the oxidation potential of the analyte, and the impedance of the detection setup depends on the analyte-loading of the sensing medium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Alcohol adsorption and transformation of alcohol into carbonyl compounds induced by MOF metal nodes would result in permittivity changes and interfacial polarization of the materials, which could be easily detected by microwave energy dissipation. However, the main focus of this work was alcohol detection, which only confirmed that the synthesized catalyst could be used for the electrooxidation of alcohol; the specific catalytic performance parameter was unknown [170].…”
Section: Electrocatalytic Oxidation Of Alcohols Using Mof-based Catal...mentioning
confidence: 92%
“…Alcohol adsorption and transformation of alcohol into carbonyl compounds induced by MOF metal nodes would result in permittivity changes and interfacial polarization of the materials, which could be easily detected by microwave energy dissipation. However, the main focus of this work was alcohol detection, which only confirmed that the synthesized catalyst could be used for the electrooxidation of alcohol; the specific catalytic performance parameter was unknown [170].…”
Section: Electrocatalytic Oxidation Of Alcohols Using Mof-based Catal...mentioning
confidence: 92%